An Analysis of Reading Comprehension Questions in the English Textbook Bahasa Inggris untuk Siswa SMA/MA Berbasis Profil Pelajar Pancasila - Beby Sinta Talaohu; Alicia Ferani Solong; Nangcy Lely Tahapary; Hanayanti; Yuni Miniaty (EduInovasi: Journal of Basic Educational Studies, 2025)
The Merdeka Curriculum was introduced to reform Indonesia's education system by fostering independent, enjoyable learning tailored to students’ interests and talents, with an emphasis on critical thinking, creativity, and problem-solving. This study evaluates the effectiveness of reading comprehension questions in the Grade 11 English textbook Bahasa Inggris untuk Siswa SMA/MA Berbasis Profil Pelajar Pancasila (published by Yrama Widya) in promoting higher-order thinking skills through Barrett's Taxonomy. Using a descriptive content analysis approach, 118 questions across 10 units were analyzed, including 53 essay, 53 multiple-choice, and 12 true/false questions. Findings indicate a strong focus on literal comprehension (64.41%), with limited emphasis on inferential comprehension (20.34%), appreciation (4.24%), reorganization (3.39%), and evaluation (7.63%). This imbalance suggests the textbook may inadequately support the Merdeka Curriculum’s goals for critical thinking and problem-solving. The study recommends a more balanced distribution of question types to better align with the curriculum’s objectives, thereby enhancing students' critical and creative thinking skills in line with educational improvement goals.